Defluorinative phosphorylation of perfluoroalkyl ketones: synthesis of fluoroalkylated and phosphorylated furan derivatives. Issue 7 (4th February 2021) - Wang, Qing-Dong; Zhang, Chen; Sun, Li-Wen; Luo, Xin-Long; Rao, Weidong; Shen, Zhi-Liang; Chu, Xue-Qiang
Abstract : An efficient method for the synthesis of fluoroalkylated tri(hetero)arylphosphine oxides from polyfluoroalkyl ketones and phosphine oxides or phosphonates has been developed. Abstract : Efficient synthesis of fluoroalkylated tri(hetero)arylphosphine oxides from perfluoroalkyl ketones and phosphine oxides or phosphonates has been achieved via successive C(sp 3 )–F bond activation under mild reaction conditions. This approach involving new C(sp 2 )–P/C(sp 2 )–O bond formation and fluoroalkylated heterocycle construction distinguishes itself by its broad substrate scope and synthetic simplicity. Moreover, tri(hetero)arylphosphines could also be prepared in high yields by further reductive transformation.